AKTIVITAS ANTIBIOFILM BAKTERI Escherichia coli OLEH BAKTERIOFAG SECARA IN VITRO [Escherichia coli biofilm in vitro eradication by bacteriophage] - Triana, Evi (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Several Escherichia coli strains are pathogenic. Excessive and noncompliant use of antibiotics and disinfectants may cause bacteria to build resistance mechanisms. Forming biofilms cause eradicatation more difficult. An effective cleaning action required antibiofilm and antimicrobial agents that have different mechanisms with antibiotics and disinfectants. Bacteriophages are potential candidates because they meet these requirements. Bacteriophages produce specific polysaccharide lyase enzymes capable of degrading biofilm extracellular polymeric matrix. Study was aimed to determine concentrations of specific bacteriophage showing Escherichia coli antibiofilm activity was conducted. The results of this study showed that the most effective concentrations bacteriophage EC RTH 04 to prevent, inhibit, and degrade Escherichia coli EC 3 biofilms were 106, 102, dan 102 respectively.